Art of the Bauhaus : Artists and Publications. (New York : Helen Serger, la boetie, inc., 1982)
Albers, Anni & Josef ; Bayer, Herbert ; Burchartz, Max ; Chagall, Marc ; Citroen, Paul ; Dexel, Walter ; Drewes, Werner ; Feininger, Lyonel ; Forbat, Fred ; Gropius, Walter ; Haffenrichter, Hans ; Hofmann, Otto ; etc.
Art of the Bauhaus : Artists and Publications, Helen Serger, la boetie, inc., New York, March 20-June 30, 1982
boek